The crosstalk between NLRP3 inflammasome and gut microbiome in atherosclerosis - Xiao-Nan Zhang; Zong-Liang Yu; Ji-Ye Chen; Xiao-Ya Li; Ze-Ping Wang; Min Wu; Long-Tao Liu (Elsevier, 2022)
Atherosclerosis (AS) is chronic pathological process based on the inflammatory reaction associated with factors including vascular endothelial dysfunction, inflammation, and autoimmunity. Inflammasomes are known to be at the core of the inflammatory response. As a pattern recognition receptor of innate immunity, the NLRP3 inflammasome mediates the secretion of inflammatory factors by activating the Caspase-1, which is important for maintaining the immune system and regulating the gut microbiome, and participates in the occurrence and development of AS. The intestinal microecology is composed of a large number of complex structures of gut microbiota and its metabolites, which play an important role in AS. The gut microbiota and its metabolites regulate the activation of the NLRP3 inflammasome. Targeting the NLRP3 inflammasome and regulating intestinal microecology represent a new direction for the treatment of AS. This paper systematically reviews the interaction between the NLRP3 inflammasome and gut microbiome in AS, strategies for targeting the NLRP3 inflammasome and gut microbiome for the treatment of AS, and provides new ideas for the research and development of drugs for the treatment of AS.